2021
DOI: 10.1111/jcmm.16670
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolaric acid B ameliorates synovial inflammation and vessel formation by stabilizing PPARγ to inhibit NF‐κB signalling pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Previous studies indicated that PPARG reduction in osteoarthritic cartilage was highly correlated with increased expression of inflammatory and catabolic factors. [41][42][43] To further validate the results of network pharmacological analysis, we first confirmed that the level of PPARG in articular cartilage of DMM-induced mice was reduced significantly, which could be rescued with E.G. treatment.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies indicated that PPARG reduction in osteoarthritic cartilage was highly correlated with increased expression of inflammatory and catabolic factors. [41][42][43] To further validate the results of network pharmacological analysis, we first confirmed that the level of PPARG in articular cartilage of DMM-induced mice was reduced significantly, which could be rescued with E.G. treatment.…”
Section: Discussionmentioning
confidence: 72%
“…At the same time, PAB inhibits NF-κB signaling by stabilizing peroxisome proliferator activated receptor γ to prevent M1 polarization and angiogenesis, thereby further reducing synovitis and OA progression ( 51 ). In vivo , mice treated with PAB show significantly reduced cartilage destruction and improved synovitis ( 52 ). These results expand the potential clinical application of PAB and strengthen the possibility that early targeting of synovitis or inhibiting angiogenesis may prevent OA ( 52 ).…”
Section: Macrophages Are Emerging Targets For Oa Treatmentmentioning
confidence: 99%
“…In vivo , mice treated with PAB show significantly reduced cartilage destruction and improved synovitis ( 52 ). These results expand the potential clinical application of PAB and strengthen the possibility that early targeting of synovitis or inhibiting angiogenesis may prevent OA ( 52 ).…”
Section: Macrophages Are Emerging Targets For Oa Treatmentmentioning
confidence: 99%
“…Specifically targeting monocyte-derived macrophages might be a more efficient strategy, due to their supposedly important role in skewing synovial macrophage phenotype as shown by the evidence presented in this review. Using factors that stabilize PPARγ could aid in skewing macrophage phenotype to become more anti-inflammatory [ 85 ]. Alternatively, inhibiting monocyte infiltration by blocking CCL2 or CCR2 (a phase 2 clinical trial using CCR antagonist CNTX-6970 is currently ongoing), or inducing innate immune tolerance via vaccination with BCG, are some of many possible options to interfere in this process in an attempt to find a novel therapy for OA.…”
Section: Implications For Therapeutic Optionsmentioning
confidence: 99%